The Effect Of Capital Adequacy Ratio and Loan To Deposit Ratio on Banking Profitability - Setiawan, Yusuf; Mulyadi, Mulyadi; Nupus, Maniyatin (Bina Bangsa International Journal of Business and Management, 2021)
The objective of this research is to analyses the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO), toward Profitability of Domestic Banks and Foreign Banks in January 2003 until December 2007. This research also used Chow Test to analyses the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO), toward Profitability between State Owned Banks and Foreign Banks. This research used time series data from Bank Indonesia’s three-monthly domestic Banks and Foreign Banks published financial reports. After passed the purposive sampling phase, the number of valid samples is 10 Domestic Banks and 10 Foreign Banks. This research used multiple regression analysis to analyses the data. This research also used Chow Test to analyses the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO), toward Profitability between Domestic Banks and Foreign Banks. Empirical evidence shows that Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) has a positive and significant influence toward profitability in State Owned Banks. And only Size has positive and significant influenced toward profitability in foreign bank. The result of this research shows that adjusted R2 from Domestic Banks is 90,2% and Foreign Banks is 45,1%. F test shows that in simultant, Domestic Banks, Foreign Banks, variable independent influence variable dependent. Chow Test result shows influence of Capital Adequacy Ratio (CAR), loan to Deposit Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO) toward Profitability between Domestic Banks and Foreign Banks. This research result can be consideration for investor in invested whether domestic bank and foreign bank. Existence global competition that always change caused domestic bank and foreign bank must follow the flow of global competition changing to maintain survive, with this competition then needed for future research